2020
DOI: 10.1016/j.psychres.2020.113441
|View full text |Cite
|
Sign up to set email alerts
|

The mental health impact of the covid-19 pandemic on healthcare workers, and interventions to help them: A rapid systematic review

Abstract: Highlights Healthcare workers’ mental health problems correlate with organizational factors such as workload and exposure to covid-19 patients. Healthcare workers are more interested in occupational protection, rest, and social support than in professional psychological help. Interventions focus more on addressing individual psychopathology, which points towards a mismatch between what workers want and need, and the services available to them.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

73
856
11
44

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 710 publications
(984 citation statements)
references
References 83 publications
73
856
11
44
Order By: Relevance
“…Moreover, the current rates of burnout among health care professionals are considered a “ticking timebomb,” as increases in burnout incidence will result in deleterious effects on health ( Hall et al, 2016 ; Dawkins and Burdess, 2020 ). Work overload, long work hours, time pressure, role conflicts, and insecurity seem to contribute to an increased risk of burnout ( Amoafo et al, 2014 ; Muller et al, 2020 ; Pappa et al, 2020 ; Seo et al, 2020 ). Indeed, as burnout rates increase among health care professionals, anxiety and depressive symptoms also become more prevalent ( Hintsa et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the current rates of burnout among health care professionals are considered a “ticking timebomb,” as increases in burnout incidence will result in deleterious effects on health ( Hall et al, 2016 ; Dawkins and Burdess, 2020 ). Work overload, long work hours, time pressure, role conflicts, and insecurity seem to contribute to an increased risk of burnout ( Amoafo et al, 2014 ; Muller et al, 2020 ; Pappa et al, 2020 ; Seo et al, 2020 ). Indeed, as burnout rates increase among health care professionals, anxiety and depressive symptoms also become more prevalent ( Hintsa et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…For comparison, the scores for the high-risk group were higher than the normative value of 12–14 in the US general population, emphasizing the immense psychological impact that healthcare crises can have on more vulnerable HCWs [ 7 ]. A similar study conducted during the SARS pandemic on HCWs found that individuals with anxious or avoidant personality traits and avoidant coping mechanisms were at higher risk of mental health stress [ 8 ]. Further, problem-focused coping strategies among HCWs during the SARS pandemic has been reported to decrease their stress and lessen their fear [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…A similar study conducted during the SARS pandemic on HCWs found that individuals with anxious or avoidant personality traits and avoidant coping mechanisms were at higher risk of mental health stress [ 8 ]. Further, problem-focused coping strategies among HCWs during the SARS pandemic has been reported to decrease their stress and lessen their fear [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations